Blood work : life and laboratories in Penang - Carsten, Janet (Lewis Henry Morgan lectures., 2019)
Janet Carsten traces the multiple meanings of blood as it moves from donors to labs, hospitals, and patients in Penang, Malaysia, showing how those meanings provide a gateway to understanding the social, political, and cultural dynamics of modern life.